Rethinking agrifood systems: Prioritizing pathways for transformation over terminologies. CGIAR Issue Brief Series for Informing COP 29 | Number 6 - Mukherji, Aditi (CGIAR Climate Change Impact Platform, 2024)
Agriculture track negotiations at the UNFCCC COPs and Subsidiary Bodies (SBs) have underscored the critical need for sustainable and resilient agricultural practices to combat climate change and ensure food security. Various terminologies are used to describe resilient and sustainable agri-food systems and approaches. But these are often misunderstood or used interchangeably, and some are contested by some constituencies and Parties. Given the wide diversity of agri-food systems, universally accepted terminologies may not be feasible. However, the focus should be less on exact terminologies, but rather on outcomes and pathways towards achieving resilient and sustainable agri-food systems.